FLEXIBLE WORKING ARRANGEMENT, WORK LIFE BALANCE, DAN KEPUASAN KERJA TERHADAP KINERJA DRIVER GOJEK DI SEMARANG - Nabila Zahra Silminisa; Aris Puji Purwatiningsih; Agus Prayitno; Sih Darmi Astuti (Universitas Pasundan, 2025)
This study aims to analyze the effect of Flexible Working Arrangement, Work Life Balance, and Job Satisfaction on Gojek driver performance in Semarang City. This study uses a quantitative approach with data collection through questionnaires distributed to active Gojek drivers. The results showed that Flexible Working Arrangement, Work Life Balance, and Job Satisfaction have a positive effect on improving driver performance, both partially and simultaneously. This finding indicates that optimal management of these three variables can encourage drivers to work more productively, loyally, and professionally. This study illustrates that the success of driver performance can be improved through support for work flexibility, work life balance, and satisfaction in their work. Gojek drivers are advised to manage their working hours flexibly but in a structured manner in order to maintain a good work-life balance. Further research is needed to examine other factors that may affect driver performance, such as burnout, work motivation, rewards, and employment insurance.